2013
DOI: 10.1136/annrheumdis-2013-204235
|View full text |Cite
|
Sign up to set email alerts
|

FGF2 induces RANKL gene expression as well as IL1β regulated MHC class II in human bone marrow-derived mesenchymal progenitor stromal cells

Abstract: ObjectiveHuman bone marrow mesenchymal stromal cells (hBM-MSC) are being applied in tissue regeneration and treatment of autoimmune diseases (AD). Their cellular and immunophenotype depend on isolation and culture conditions which may influence their therapeutic application and reflect their in vivo biological functions. We have further characterised the phenotype induced by fibroblast growth factor 2 (FGF2) on healthy donor hBM-MSC focusing on the osteoimmunological markers osteoprotegerin (OPG), receptor act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 50 publications
4
15
1
Order By: Relevance
“…To the best of our knowledge, this hypothesis has not been addressed in detail in literature. In a recent article, the authors could detect RANK expression in human BM‐MSCs only in the presence of FGF2 in the culture medium ; however, this discrepancy with our own result might derive from different conditions of isolation, culture and expansion. Therefore, further evaluating the possibility of a RANKL/RANK axis in MSCs could be highly relevant, considering that the RANKL molecule is a target of anti‐resorptive treatments in humans.…”
Section: Discussioncontrasting
confidence: 97%
“…To the best of our knowledge, this hypothesis has not been addressed in detail in literature. In a recent article, the authors could detect RANK expression in human BM‐MSCs only in the presence of FGF2 in the culture medium ; however, this discrepancy with our own result might derive from different conditions of isolation, culture and expansion. Therefore, further evaluating the possibility of a RANKL/RANK axis in MSCs could be highly relevant, considering that the RANKL molecule is a target of anti‐resorptive treatments in humans.…”
Section: Discussioncontrasting
confidence: 97%
“…It is well known that the cellular and immunophenotype of hMSC depend not only on the isolation protocol but also on the culture conditions. 57,58 Our results showed that both bioreactor types were able to maintain the hMSC cellular phenotype; hMSC were negative for hematopoietic CD34 and CD45 markers and displayed high levels of CD44, CD73, CD105, CD90, and CD166 mesenchymal stem markers ( Figures 6A and B). According to the International Society for Cellular Therapy, hMSC are also considered HLA-DR-negative with no/reduced (below 5%) expression of HLA-DR surface molecules.…”
Section: Hmsc Productionmentioning
confidence: 84%
“… 27 TNF-α can promote the secretion of Hepatocyte growth factor by BMSCs through p38 MAPK and PI3K/Akt pathways. 28 Thus, NF-κB, ERK and c-Jun-NH2-terminal Kinase (JNK) pathways play an essential role for migration homing and adhesion of BMSCs. 29 …”
Section: Discussionmentioning
confidence: 99%